DEMOGRAPHIC FACTORS AND KNOWLEDGE LEVEL INFLUENCED IMPLEMENTATION OF POSTPARTUM GYMNASTIC IN NORMAL POSTPARTUM MOTHER - Syaiful, Yuanita; Qomariah, Siti Nur; Fatmawati, Lilis; Barrotul, Umi (jfpublisher, 2022)
Introduction. Postpartum gymnastic are motion exercise that are performed as soon as possible after giving birth, so that the muscles that experience stretching during pregnancy and childbirth can return to normal conditions as before. This study aimed to analyzed demographic factors and knowledge level with the implementation of postpartum gymnastic in normal postpartum mother. Method. This research design used cross sectional method. The sampling method used purposive sampling with criteria: normal postpartum mother with age 18-45 years old. Samples were taken in Sidokumpul Bungah Gresik village with 30 respondents for two months from population of 32 respondents. The independent variables were demographic factors (information resource, employment, education level, and parity) and knowledge level. The dependent variable was the implementation of postpartum gymnastic. The instruments used were questionnaires and implementation of postpartum gymnastic check list. The research data were analyzed using Regression Linier. Result & Analysis. The results of the Linear Regression statistical test showed that demographic factors (sources of information, employment, and education) and the level of knowledge affect the implementation of postpartum gymnastic in normal postpartum mothers. The correlation number for the level of knowledge is the greatest (r = 0.785) so that it has the strongest level of influence of the relationship with the implementation of postpartum gymnastic. The relationship between the two variables is unidirectional, so it means that the level of knowledge is increased then the implementation of postpartum gymnastic will increase. Discussion.This research is expected to be able to make information on nurse intervention increase patient knowledge in the implementation of postpartum gymnastic so as to help accelerate recovery of postpartum mothers.